Effects of CD34+ cell dose on haematopoietic recovery in acute lymphoblastic leukaemia patients with positive pretransplant measurable residual disease. (4th October 2022) - Wang, Yuewen; Mo, Xiaodong; Cheng, Yifei; Chen, Yuhong; Lv, Meng; Wang, Fengrong; Yan, Chenhua; Han, Wei; Chen, Huan; Xu, Lanping; Wang, Yu; Zhang, Xiaohui; et al.
Abstract: Introduction: A higher CD34 + cell dose in allografts is associated with faster haematopoietic recovery after allogeneic haematopoietic stem cell transplantation (allo‐HSCT). Leukaemia stem cells impair normal bone marrow (BM) niches and induce BM failure during leukemogenesis. However, whether measurable residual disease (MRD), known as the persistence of low‐level leukaemic cells, could influence the effects of CD34 + cell dose on haematopoietic recovery after transplantation in acute lymphoblastic leukaemia (ALL) patients is unknown. Methods: A total of 975 ALL patients were enrolled and classified into pre‐HSCT MRD‐positive and MRD‐negative subgroups. Cox proportional hazard regression models were built for time‐to‐event outcomes. Multivariate analysis was performed to determine independent influencing factors from the univariate analysis. Results: An appropriate CD34 + cell dose was positively associated with faster haematopoietic recovery in the total ALL population. More importantly, in pre‐HSCT MRD‐positive ALL patients, a higher CD34 + cell dose (≥2.76 × 10 6 /kg) was related to faster neutrophil (HR 1.330, 95% CI 1.045–1.692, p = 0.021) and platelet engraftment (HR 1.808, 95% CI 1.412–2.316, p < 0.001) in multivariate analysis. CD34 + cell dose was a crucial factor associated with either engraftment or transplant outcomes, although we did not demonstrate direct correlations of CD34 + cell dose with relapse, TRM, LFS or OS after allo‐HSCT. Conclusion: Our results indicated that no additional CD34 + stem and progenitor cell harvests were needed to ensure successful haematopoietic recovery in pre‐HSCT MRD‐positive patients compared to pre‐HSCT MRD‐negative patients.